Peningkatan Pendapatan Dengan Memberdayakan Keterampilan Di Desa Perdamaian Kecamatan Kota Kuala Simpang Kebupaten Aceh Tamiang - Meri Andriani; Nazaruddin; Erni Junaida (CV. ALIM'SPUBLISHING, 2024)
Many businesses experienced losses due to the Covid-19 pandemic, one of which was Mitra who was laid off from his job due to his business going bankrupt. Partners have cake-making skills that they acquired while working. Mitra wants to open his own business but doesn't have the capital so he can't afford cake ingredients and machines. There are two problems with Partners, namely the production sector, Partners do not have capital and marketing problems, Partners do not know how to market their products. The goal of service is that partners have income and the business they run runs and develops. As a result of dedication, the provision of an oven machine has resulted in Mitra getting a lot of orders, as can be seen from the evaluation carried out over seven days of orders, usually only 3 bolus cakes every day, but now it can reach 15 bolus cakes every day. In conclusion, the oven provided by the Service Team is the result of a discussion group forum which is really needed by Partners. Partner's income has increased since the Service Team provided the oven to Partners as seen from the evaluation carried out by the Service Team